Glucocorticoids Preferentially Influence Expression of Nucleoskeletal Actin Network and Cell Adhesive Proteins in Human Trabecular Meshwork Cells - Bachman, William; Maddala, Rupalatha; Chakraborty, Ayon; Eldawy, Camelia; Skiba, Nikolai P.; Rao, Ponugoti V. (Frontiers in Cell and Developmental Biology, 2022)
Clinical use of glucocorticoids is associated with increased intraocular pressure (IOP), a major risk factor for glaucoma. Glucocorticoids have been reported to induce changes in actin cytoskeletal organization, cell adhesion, extracellular matrix, fibrogenic activity, and mechanical properties of trabecular meshwork (TM) tissue, which plays a crucial role in aqueous humor dynamics and IOP homeostasis. We have a limited understanding however, of the molecular underpinnings regulating these myriad processes in TM cells. To understand how proteins including cytoskeletal and cell adhesion proteins that are recognized to shuttle between the cytosolic and nuclear regions to influence gene expression and other cellular activities, we used proteomics analysis to characterize the nuclear protein fraction of dexamethasone (Dex) treated human TM cells. Treatment of human TM cells with Dex for one, five or seven days led to consistent increases (by ≥ two-fold) in the levels of various actin cytoskeletal regulatory, cell adhesive, and vesicle trafficking proteins. Increases (≥ two-fold) were also observed in levels of Wnt signaling regulator (glypican-4), actin binding chromatin modulator (BRG1) and nuclear actin filament depolymerizing protein (MICAL2; microtubule associated monooxygenase, calponin and LIM domain containing), together with a decrease in tissue plasminogen activator. These changes were independently further confirmed by immunoblotting analysis. Interestingly, deficiency of BRG1 expression blunted the Dex-induced increases in the levels of some of these proteins in TM cells. Collectively, these findings indicate that the widely recognized changes in actin cytoskeletal and cell adhesive attributes of TM cells by glucocorticoids involves actin regulated BRG1 chromatin remodeling, nuclear MICAL2, and glypican-4 regulated Wnt signaling upstream of the serum response factor/myocardin controlled transcriptional activity.